ANALISIS TIMBAL DALAM LINDI (Leachate) SECARA KOAGULASI MENGGUNAKAN POLIALUMINIUM KLORIDA - Astrianty Unwakoly; Nikmans Hattu; Yeanchon H Dulanlebit (Molluca Journal of Chemistry Education (MJoCE), 2019)
Leachate is a liquid arising from the decomposition of waste that has decayed due to the flow of external water into the landfill. Leachate can be toxic. generally, leachate contains several high inorganic metals, including lead. Lead is one type of heavy metal that has a high toxicity. This study aims to determine the initial concentration of lead (Pb) in leachate and the percent efficiency of polyaluminium chloride (PAC) coagulant in reducing lead levels in IPST Toisapu, Ambon City. Lead content was analyzed by coagulation using an atomic absorption spechtrophotometer (AAS). Coagulation is a chemichal process used to remove particles that can cause environmental pollution. The coagulant used is a polyaluminium chloride coagulant. The results of the analysis showed that the initial lead concentration at IPST Toisapu was 2.7670mg/L and the percentage of PAC coagulant efficiency was 500, 600, 700, 800 and 1000 mg/L respectively 61,59%; 69,92%; 73,55%; 77,17% and 84,79%. The results showed that PAC coagulant was effective in reducing lead levels in leachate.